Probiotics in dentistry: review of the current status - Reddy, Jaddu Jyothirmai; Sampathkumar, Naganandini; Aradhya, Shankar (Archives of Oral Research, 2010)
Objective: The aim of this comprehensive review is to present an update about the current status ofprobiotics in terms of its application in the fi eld of dentistry. Background: The concept of administrationof benefi cial bacteria with a view to replace harmful microbes with useful ones has been revived bythe probiotic concept. The main fi eld of research has been in the gastrointestinal tract. However, pastfew years has seen investigation of probiotics from the oral health perspective. Probiotic approach hasshown promising results in oral cavity with respect to control of chronic disease such as dental caries,periodontitis, and recurring problems like halitosis and candidial infections. Control of biofi lm formationon voice prosthesis has also been documented. Conclusion: Despite the immense potential of probiotics,data is still defi cient on the probiotic action in the oral cavity. Further double-blind, randomized,placebo-controlled trials are needed before any concrete clinical recommendations can be made.